Complexity of mentalization - Arabadzhiev, Zlatoslav; Paunova, Rositsa (Frontiers in Psychology, 2024)
Mentalization is empirically associated with resolving psychological tasks in normative dilemmas and also, can influence on the outcome of personal and situational crises. And so forth, passing through the different stages of life and prevention of dysfunctional patterns in the family is facilitated. The ability to understand other people's emotions, thoughts, and behaviours is associated with an individual's ability and his attitude in the context of relationships. The topic is very modern in everyday life, as well as is one of the cutting edges in the modern psychotheraputic approach.